Tailoring Self‐Polarization of Bimetallic Organic Frameworks with Multiple Polar Units Toward High‐Performance Consecutive Multi‐Band Electromagnetic Wave Absorption at Gigahertz. (11th March 2022) - Cheng, Junye; Zhang, Huibin; Wang, Honghan; Huang, Zehao; Raza, Hassan; Hou, Chuanxu; Zheng, Guangping; Zhang, Deqing; Zheng, Qingbin; Che, Renchao
Abstract: Multiple relaxation behaviors are promising for broad frequency band and strong electromagnetic wave (EMW) absorption based on polarization‐controlled electromagnetic (EM) attenuation. However, rational selection of materials and structure manipulation through tunable substitution or phase control are challenging toward optimization of EMW absorption. Herein, bi‐metallic organic frameworks (B‐MOFs) with various morphologies are employed as EMW absorbers. Remarkably, the polar units can be enhanced by introducing Ni‐metal nodes into the Cu‐coordinated MOFs, rendering the B‐MOFs with self‐polarized properties and consecutive multifrequency EMW absorption behaviors. The maximum reflection loss of acetylene black (ACET) filled NiCu‐MOFs can reach –40.54 dB together with a wide bandwidth (<‐10 dB) of 5.87 GHz at a thickness of 2.5 mm. As a counterpart of the Ni/Cu/C derivatives, significantly increased broad band absorption (6.93 GHz) and multifrequency absorbing and polarization characteristics are also maintained in bimetal coexisting carbonized architectures as prepared by calcination of CuNi‐MOFs. This work demonstrates that the performance of effective absorbing frequency band can be enhanced in multi‐metallic organic frameworks‐based architectures, and paves a novel avenue for developing broadband and strong EMW absorbers. Abstract : Bi‐metallic organic frameworks (B‐MOFs) with various morphologies are successfully constructed via a one‐step solvothermal route. Combined with a facile physical filling route using acetylene black (ACET), the mixtures of CuNi‐MOFs/ACET exhibit superior electromagnetic wave (EMW) absorption performance. Remarkably, the polar units enhanced by introducing Ni‐metal nodes in the Cu‐MOFs render the B‐MOFs with self‐polarized properties and consecutive multifrequency EMW absorption behaviors.